Dissemination of Health-Related Research among Scientists in Three Countries: Access to Resources and Current Practices - Tabak, Rachel G. (Biomed Res Int, 2015)
Objectives. In public health and clinical settings insufficient dissemination of evidence-based practices limits the reach of new discoveries to broad populations. This study aimed to describe characteristics of the dissemination process by researchers across three countries (Brazil, United Kingdom, and United States), explore how designing for dissemination practices has been used, and analyze factors associated with dissemination. Methods. A similar online survey was used to query researchers across the three countries; data were pooled to draw cross-country conclusions. Findings. This study identified similarities and differences between countries. Importance of dissemination to nonresearcher audiences was widely recognized as important; however, traditional academic venues were the main dissemination method. Several factors were associated with self-rated dissemination effort in the pooled sample, but these predictive factors (e.g., support and resources for dissemination) had low prevalence. Less than one-third of researchers rated their level of effort for dissemination as excellent. Respondents reported limited support and resources to make it easier for researchers who might want to disseminate their findings. Conclusion. Though intentions show the importance of dissemination, researchers across countries lack supports to increase dissemination efforts. Additional resources and training in designing for dissemination along with improved partnerships could help bridge the research-practice gap.